Meningeal Carcinomatosis and Uterine Carcinoma: Three Different Clinical Settings and Review of the Literature. Issue 1 (1st January 2009) - Asensio, Nuria; Luis, Ana; Costa, Ilda; Oliveira, João; Vaz, Fátima
Abstract : Introduction: Leptomeningeal carcinomatosis is a rare metastatic event in gynecological neoplasias, and most cases occur in ovarian cancer. It is extremely infrequent in cervical cancer, and so far, there are not any reports of this complication in association with endometrial cancer. Patients and Methods: We report a case of leptomeningeal carcinomatosis secondary to endometrial carcinoma and 2 complex cervix cancer cases. A MEDLINE search was done to review all published cases of this complication in gynecological cancer to identify predictive factors for this diagnosis. Results and Discussion: Leptomeningeal carcinomatosis is usually diagnosed late in the course of the disease, and most reports concern ovarian cancer patients. The number of cases describing this neurologic complication in cervix cancer is increasing. Gadolinium-enhanced magnetic resonance imaging may be necessary for this diagnosis, because cerebrospinal fluid analysis results may be negative. Most cervix cases had squamous cell (8/14) or neuroendocrine histologic subtype (3/14), and when reported, differentiation was usually poor. The case we report of endometrial carcinoma, unique in the literature, is a serous adenocarcinoma. Conclusions: A high index of suspicion is necessary, and leptomeningeal carcinomatosis should be considered in patients with unexplained neurologic symptoms whose gynecologic tumors are poorly undifferentiated or have a serous component.